Bioethics and professional identity: the healthcare worker's construction of the experience of him/herself¹ - Flávia Regina Souza Ramos; Jorge Ramos Do Ó (Faculdade de Medicina de Botucatu (Unesp), 2010)
This study approaches bioethics as discourse inside broad cultural changes and also in its growing impacts on the constitution of the healthcare professional's identity. Two theses, based on Giddens' theoretical framework, are presented. The first is that bioethics potentially is an abstract system that is capable of producing reflection and of organizing the experience and the subjective identity project of the healthcare worker; the second states that the ethical/bioethical education of the healthcare worker is inseparable from a set of pedagogical devices that relate work and formal education in "modes of being professional". Professional identity is discussed in the context of the decentralization of the modern subject and new notions of personal identities, as well as within pedagogical devices that are strongly aligned with the political and technical demands and configurations of concrete work scenarios, capable of defining the moral/ethical potential of the formal education offered.